Structural and functional studies of a Fusarium oxysporum cutinase with polyethylene terephthalate modification potential - Dimarogona, Maria; Nikolaivits, Efstratios; Kanelli, Maria; Christakopoulos, Paul; Sandgren, Mats; Topakas, Evangelos (Biochimica et biophysica acta, 2015)
Cutinases are serine hydrolases that degrade cutin, a polyester of fatty acids that is the main component of plant cuticle. These biocatalysts have recently attracted increased biotechnological interest due to their potential to modify and degrade polyethylene terephthalate (PET), as well as other synthetic polymers. A cutinase from the mesophilic fungus Fusarium oxysporum, named FoCut5a, was expressed either in the cytoplasm or periplasm of Escherichia coli BL21. Its X-ray structure was determined to 1.9Å resolution using molecular replacement. The activity of the recombinant enzyme was tested on a variety of synthetic esters and polyester analogues. The highest production of recombinant FoCut5a was achieved using periplasmic expression at 16°C. Its crystal structure is highly similar to previously determined Fusarium solani cutinase structure. However, a more detailed comparison of the surface properties and amino acid interactions revealed differences with potential impact on the biochemical properties of the two enzymes. FoCut5a showed maximum activity at 40°C and pH8.0, while it was active on three p-nitrophenyl synthetic esters of aliphatic acids (C2, C4, C12), with the highest catalytic efficiency for the hydrolysis of the butyl ester. The recombinant cutinase was also found capable of hydrolyzing PET model substrates and synthetic polymers. The present work is the first reported expression and crystal structure determination of a functional cutinase from the mesophilic fungus F. oxysporum with potential application in surface modification of PET synthetic polymers. FoCut5a could be used as a biocatalyst in industrial applications for the environmentally-friendly treatment of synthetic polymers. •A cutinase from F. oxysporum was functionally expressed in the periplasm of E. coli.•FoCut5a X-ray structure was determined to 1.9Å resolution.•The cutinase was active on a variety of synthetic esters and polyester analogues.•FoCut5a could be used for the surface modification of PET synthetic polymers.